An Overview of the Role of Radiotherapy in the Treatment of Small Cell Lung Cancer – A Mainstay of Treatment or a Modality in Decline?. Issue 11 (November 2022) - Merie, R.; Gee, H.; Hau, E.; Vinod, S.
Abstract: Aims: Small cell lung cancer (SCLC) accounts for about 15% of all lung cancers. Chemotherapy, immunotherapy and radiotherapy all play important roles in the management of SCLC. The aim of this study was to provide a comprehensive overview of the role and evidence of radiotherapy in the cure and palliation of SCLC. Materials and methods: The search strategy included a search of the PubMed database, hand searches, reference lists of relevant review articles and relevant published abstracts. ClinicalTrials.gov was also queried for relevant trials. Results: Thoracic radiotherapy improves overall survival in limited stage SCLC, but the timing and dose remain controversial. The role of thoracic radiotherapy in extensive stage SCLC with immunotherapy is the subject of several ongoing trials. Current evidence supports the use of prophylactic cranial irradiation (PCI) for limited stage SCLC but the evidence is equivocal in extensive stage SCLC. Whole brain radiotherapy is well established for the treatment of brain metastases but evidence is rapidly accumulating for the use of stereotactic radiosurgery. Further studies will define the role of PCI, whole brain radiotherapy and hippocampal avoidant PCI in the immunotherapy era. Conclusion: Radiotherapy is an essential component in the multimodality management of SCLC. Technological advances have allowed safer delivery of radiotherapy with reduced toxicities. Discussion at multidisciplinary team meetings is important to ensure radiotherapy is considered and offered in appropriate patients. Highlights: Radiotherapy has an important role in both the cure and palliation of SCLC. Technological advances allow safer delivery of thoracic radiotherapy with reduced toxicities. Role of thoracic radiotherapy in the immunotherapy era is uncertain and is a subject of ongoing trials. Hippocampal avoidance PCI in LS-SCLC may reduce neurotoxicity without compromising outcomes. Shared decision making on PCI versus MRI surveillance in ES-SCLC is essential.